The role of engineering in the management of public works: training and professional performance - Magalhães, Stenio Luis Costa; Valente, Maria José Paes (Brazilian Journal of Production Engineering, 2020)
This article addresses relevant issues related to the performance of the engineer in public construction management, emphasizing the importance of obtaining specific knowledge during his academic formation in order to accumulate information for good professional practice in this area.The general objective of the research was to identify gaps in the curricula of two important universities in Maranhão that hinder the formation of engineers who intend to work in public engineering, since there are specificities in the stages of planning, execution and management of a public construction that require specific professional skills and that should be made available in academic enviroment. In addition, we sought to identify the profile of the professional who works in public engineering, through the application of a questionnaire and face-to-face interview to understand their difficulties, suggestions, in order to establish a relationship between their academic formation and their professional performance. We present and discuss essential topics for good professional performance. The delimitation of these themes was based on extensive bibliographic research, as well as on the author’s professional experience. Thus, the deficiencies found in the training of the professional who intends to work in public engineering were demonstrated, and the research can contribute to the updating of the curricula with regard to training for this specific area. Through the curriculum analysis of two major universities of higher education in the state of Maranhão, gaps are identified related to issues pertaining to generalist education that should also cover the areas of management, administration, leadership, environmental, legal. This outdated curriculum is reflected in the inefficient performance of the civil engineer in the performance of management and supervision activities in relation to public works, a fact verified in the research through the answers of the investigated professionals. Thus, we intend to contribute to the updating of curricula by offering subsidies to overcome the deficiencies found in the education of professionals who intend to work in public engineering. ers of the investigated professionals. Thus, we intend to contribute to the updating of curricula by offering subsidies to overcome the deficiencies found in the education of professionals who intend to work in public engineering.